Effect of Exercise in the Prevention and Management of Type 2 Diabetes Mellitus (Pulse, 2014)
Physical activity (PA) is a key element in the prevention and management of type 2 diabetes but it is now well established that participation in regular PA improves blood glucose control and can prevent or delay the type 2 diabetes along with affecting lipids, blood pressure, cardiovascular events, mortality and quality of life. Structured interventions combining PA and modest weight loss have been shown to lower type 2 diabetes risks by up to 58% in high-risk populations. Most benefits of PA on diabetes management are realized through acute and chronic improvements in insulin action, gestational diabetes mellitus, and safe and effective practices for PA with diabetes-related complication. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20346 Pulse Vol.6 January-December 2013 p.33-36